Information Systems for Useful Innovation in Enterprises. Editorial Introduction to Issue 37 of CSIMQ - Emanuele Laurenzi (Complex Systems Informatics and Modeling Quarterly)
Innovation contributes to the economic and societal growth of nations, it creates new jobs, new business models, and new revenue streams as well as allows for the resolution of ever-evolving human needs. Enterprises that aim to thrive in the market must allocate resources and time to innovate besides the usual productivity focus. Innovating, however, is a very challenging task because it requires a high level of knowledge and creativity. Digital transformation (DT), in turn, is the process of adoption and use of digital technologies by an enterprise and sets the scenes for innovation. Further, to be useful for enterprises, innovation solutions should be incorporated into well-established company realities, which is a grand challenge nowadays. Methodological approaches are essential to tackle such a grand challenge. The Information Systems (IS) discipline, which is continuously involved in building its research knowledge base that is relevant to practice, is at the forefront for the creation of methodological approaches for useful innovation in enterprises, which is the central theme of this issue of CSIMQ.